Find g(x), where g(x) is the reflection across the x-axis of f(x)=–8|x–2|+3.g(x)=8|x–2|+3g(x)=8|x–2|–3g(x)=–8|x–2|–3g(x)=–8|x–2|+3Submit

Question

Find g(x), where g(x) is the reflection across the x-axis of f(x)=–8|x–2|+3.g(x)=8|x–2|+3g(x)=8|x–2|–3g(x)=–8|x–2|–3g(x)=–8|x–2|+3Submit
🧐 Not the exact question you are looking for?Go ask a question

Solution 1

The reflection of a function across the x-axis simply changes the sign of the output of the function. So, if f(x) = -8|x-2|+3, then the reflection of f(x) across the x-axis, which we'll call g(x), is g(x) = 8|x-2|+3. This is because the absolute value function |x-2| is always positive, and the negat Knowee AI StudyGPT is a powerful AI-powered study tool designed to help you to solve study prob

Knowee AI StudyGPT is a powerful AI-powered study tool designed to help you to solve study problem.
Knowee AI StudyGPT is a powerful AI-powered study tool designed to help you to solve study problem.
Knowee AI StudyGPT is a powerful AI-powered study tool designed to help you to solve study problem.
Knowee AI StudyGPT is a powerful AI-powered study tool designed to help you to solv

This problem has been solved

Similar Questions

Find g(x), where g(x) is the reflection across the x-axis of f(x)=–8|x–2|+3.g(x)=8|x–2|+3g(x)=8|x–2|–3g(x)=–8|x–2|–3g(x)=–8|x–2|+3Submit

Find g(x), where g(x) is the reflection across the y-axis of f(x)=5|x+5|–3.g(x)=–5|x–5|+3g(x)=5|x–5|–3g(x)=5|x+5|+3g(x)=–5|x+5|–3Submit

Find g(x), where g(x) is the reflection across the y-axis of f(x)=–2x–8.g(x)=2x+8g(x)=2x–8g(x)=–2x–8g(x)=–2x+8Submit

Find g(x), where g(x) is the reflection across the x-axis of f(x)=x2–1.g(x)=x2–1g(x)=–x2–1g(x)=–x2+1g(x)=x2+1Submit

Find g(x), where g(x) is the reflection across the y-axis of f(x)=–10x+9.g(x)=–10x–9g(x)=10x+9g(x)=–10x+9g(x)=10x–9Submit

1/3